2018
DOI: 10.1162/jocn_a_01265
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Facial Slivers

Abstract: We report here an unexpectedly robust ability of healthy human individuals ( n = 40) to recognize extremely distorted needle-like facial images, challenging the well-entrenched notion that veridical spatial configuration is necessary for extracting facial identity. In face identification tasks of parametrically compressed internal and external features, we found that the sum of performances on each cue falls significantly short of performance on full faces, despite the equal visual information available from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Apparent stretching was achieved by compressing the horizontal dimension to change the aspect ratio of the headshot while holding constant the maximum vertical dimension of the images rather than increasing the vertical dimension and holding the horizontal dimension constant. This differs from Hole's original stimulus manipulation but is consistent with other studies exploring extreme variations in degrees of stretching (e.g., Gilad-Gutnick et. al., 2018).…”
Section: Stimulisupporting
confidence: 87%
“…Apparent stretching was achieved by compressing the horizontal dimension to change the aspect ratio of the headshot while holding constant the maximum vertical dimension of the images rather than increasing the vertical dimension and holding the horizontal dimension constant. This differs from Hole's original stimulus manipulation but is consistent with other studies exploring extreme variations in degrees of stretching (e.g., Gilad-Gutnick et. al., 2018).…”
Section: Stimulisupporting
confidence: 87%
“…A similar anomaly persists about why only humans have a chin [27]. The high weightage the brain assigns to interpreting patterns as faces (as seen in pareidolia [96]) and the manner in which exaggerated or distorted portions of faces in caricatures [42] are distinctly identifiable, is evidence of a plasticity in communication between the various cells that identify shapes and associate them with various parts of the brain. Researchers have identified a sensory homunculus, which represents a map of brain areas dedicated to sensory processing for different anatomical divisions of the body.…”
Section: Some Human Abilitiesmentioning
confidence: 99%
“…Nonetheless, it is been observed that the anonymous data can also be used for illegal purposes. The work of S. Gilad-Gutnick et al [13] have showcased that, from an anonymous facial video dataset, the actual personal information can be extracted. Hence, the work by S. Stalla-Bourdillon et al [12] is criticized by other researchers.…”
Section: Data Encryption Fundamentals and Parallel Research Outcmentioning
confidence: 99%